Education as a snakes and ladders game - Kundu, Deepanshu (Seminar)
FOR the past two years an elementary education programme known as Para-Lekha has been in operation in four gram panchayats in Birbhum district, West Bengal. Started in the aftermath of the first Covid lockdown in 2020, Para-Lekha aimed to utilize Self Help Group members to provide free of cost lessons on basic language and numerical skills to children who, unlike their urban counterparts, lacked access to online education during the prolonged school closures. The extent and progress of learning over time is ascertained by subjecting students to periodic testing on various indices such as alphabet recognition, reading comprehension, and the ability to add, subtract and divide. - Reproduced